What drives euro area financial market developments? The role of US spillovers and global risk - Lennart Brandt; Arthur Saint Guilhem; Maximilian Schröder; Ine Van Robays (European Central Bank (ECB), 2021)
Financial asset prices contain a rich set of real-time information on the economy. To extract this information, it is crucial to understand the driving factors behind financial market developments. In this paper, we exploit daily cross-asset price movements in a sign-restricted BVAR model to analyse the extent to which euro area and US yields, equity prices, and the euro-US dollar exchange rate are jointly driven by monetary policy, macro and global risk factors. A novelty is that we allow for cross-Atlantic spillovers while also accounting for the unique role of the US in the global financial system. Our results underline the importance of US spillovers and shifts in global risk sentiment for understanding the dynamics of euro area financial variables. Euro area shocks transmit much less to US financial markets in comparison, with global risk shocks being more important instead. Using the daily shocks as instruments in a Proxy-SVAR, we demonstrate that the transmission of financial market movements to the macroeconomy depends on the underlying driver, thereby illustrating why it matters to look into the driving factors in the first place.
Keywords: C32; C54; E44; E52; 330; International transmission; financial conditions; monetary policy; large-scale assetpurchases; high-frequency identification